Correlation of Sensation Seeking with Entrepreneurship: Study on Fresh Graduate Universitas Syiah Kuala - Mirza, Rahmad; Aprilia, Eka Dian (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2017)
Nowadays, getting a job is very difficult, there is no guarantee for a graduate to get a job. One of the alternatives is to become an entrepreneur. To become an entrepreneur needs self-confidence, responsibility, decision making skill, perseverance and risk taking which are in accordance with the dimensions of sensation seeking i.e. thrill and adventure seeking, experience seeking, disinhibition, and boredom susceptibility. This study aimed to understand the sensation seeking and entrepreneurship of the fresh graduates in The University of Syiah Kuala. The samples were 120 fresh graduates who were selected with quota sampling technique. There were two instruments used, Brief Sensation Seeking adaptation Scale (BSSS-8) by Hoyle et al (2002) consisting of 8 items and an Entrepreneurship Scale based on Kohâs theory (1996) consisting of 24 items. Data analysis result using Pearson correlation technique showed a correlation coefficient of (r) 0,714 with p value = 0,000 (p < 0,05). The proposed hypothesis was confirmed therefore it can be concluded that there was a positive and significant correlation between sensation seeking and entrepreneurship of the fresh graduates in The Universitas Syiah Kuala.